1984
DOI: 10.1007/bf00361089
|View full text |Cite
|
Sign up to set email alerts
|

Failure of bone scanning to detect fractures in a woman on chronic steroid therapy

Abstract: Osteopenic bones in patients on chronic steroid therapy are often difficult to assess for occult fractures. Such patients are also at greater risk for fractures. Technetium 99m bone scan is currently thought to represent the most sensitive method of diagnosing these lesions. We present a case of failure of diagnosis of a subtle fracture by Tc-99m bone scan and speculate on the role of steroid therapy in the mechanism of this failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Poor renal function is suspected of contributing to reduced tissue clearance of the radionuclide, with resultant poor images. Scott et al [19] reported a case in which a 33-year-old post-renal-transplant patient sustained an acute intertrochanteric fracture which bone scan did not detect. The diagnosis was made with plain film polytomography and the patient underwent surgical repair.…”
Section: Discussionmentioning
confidence: 97%
“…Poor renal function is suspected of contributing to reduced tissue clearance of the radionuclide, with resultant poor images. Scott et al [19] reported a case in which a 33-year-old post-renal-transplant patient sustained an acute intertrochanteric fracture which bone scan did not detect. The diagnosis was made with plain film polytomography and the patient underwent surgical repair.…”
Section: Discussionmentioning
confidence: 97%
“…Although the bone scan is considered the most sensitive method for detecting stress fractures [21], it involves ionizing radiation and its use for monitoring stress fracture healing was discouraged by Moran et al [18]. An additional limitation of this and other imaging tools used for stress fracture diagnosis (eg, MRI, CT, or conventional bone radiography) is that they may not be readily available in the field, particularly for soldiers in training presenting with symptoms compatible with stress fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Bone scintigraphy is not recommended in acute trauma. MRI is quicker and more specific (30,31) and there is a risk of false negative outcome when bone scanning is performed too early, especially in elderly patients and in patients with metabolic diseases (32)(33)(34). However, in stress fracture bone scintigraphy is a highly sensitive imaging modality.…”
Section: Discussionmentioning
confidence: 99%